2015
DOI: 10.1111/apm.12351
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal vaccines: a paradigm shift in the development of mucosal adjuvants and delivery vehicles

Abstract: Mucosal immune responses are the first-line defensive mechanisms against a variety of infections. Therefore, immunizations of mucosal surfaces from which majority of infectious agents make their entry, helps to protect the body against infections. Hence, vaccinization of mucosal surfaces by using mucosal vaccines provides the basis for generating protective immunity both in the mucosal and systemic immune compartments. Mucosal vaccines offer several advantages over parenteral immunization. For example, (i) eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 135 publications
(138 reference statements)
0
37
0
Order By: Relevance
“…The use of mucosal vaccines triggers local and systemic responses limiting the pathogens at the site of entry, reducing their replication in epithelial cells, the alteration of the epithelial barrier, and the action of toxins on the mucosa. In addition, mucosal vaccination helps preventing the spread of the pathogen to internal tissues and to the environment (17,18). Despite the several advantages of mucosal vaccination, it faces many difficulties including poor immunogenicity at low concentrations, chemical and enzymatic degradation, potential toxicity, and the risk of generating tolerance rather than protective immunity (17,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of mucosal vaccines triggers local and systemic responses limiting the pathogens at the site of entry, reducing their replication in epithelial cells, the alteration of the epithelial barrier, and the action of toxins on the mucosa. In addition, mucosal vaccination helps preventing the spread of the pathogen to internal tissues and to the environment (17,18). Despite the several advantages of mucosal vaccination, it faces many difficulties including poor immunogenicity at low concentrations, chemical and enzymatic degradation, potential toxicity, and the risk of generating tolerance rather than protective immunity (17,19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mucosal vaccination helps preventing the spread of the pathogen to internal tissues and to the environment (17,18). Despite the several advantages of mucosal vaccination, it faces many difficulties including poor immunogenicity at low concentrations, chemical and enzymatic degradation, potential toxicity, and the risk of generating tolerance rather than protective immunity (17,19). In this work, we demonstrated that IBLP derived from highly efficient immunomodulatory lactobacilli are an interesting alternative as mucosal adjuvants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when it comes to L. plantarum, the oral route is of interest, because this food-grade bacterium is a natural resident of the intestinal microflora (48,49). Mucosal immunization is potentially highly advantageous in vaccinology since the majority of pathogens enter the body via mucosal surfaces and it has been established that mucosal vaccination generates both mucosal and systemic immune protection (47,50).…”
Section: Discussionmentioning
confidence: 99%
“…12 The functionality and development of both delivery systems and immunostimulators as adjuvants are reviewed elsewhere. 6,[13][14][15][16][17][18][19] Aluminum-based adjuvants have been extensively used in human vaccines for almost a century, and for most of that period no other adjuvants were approved for human use. 20 The adjuvant effects of aluminum-based adjuvants were empirically discovered, while the exact mechanisms of action have remained relatively obscure until recently.…”
mentioning
confidence: 99%